1997
DOI: 10.1128/jb.179.22.6921-6928.1997
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium meliloti mutants deficient in phospholipid N-methyltransferase still contain phosphatidylcholine

Abstract: Phosphatidylcholine (PC) is the major membrane-forming phospholipid in eukaryotes. In addition to this structural function, PC is thought to play a major role in lipid turnover and signalling in eukaryotic systems. In prokaryotes, only some groups of bacteria, among them the members of the family Rhizobiaceae, contain PC. To understand the role of PC in bacteria, we have studied Rhizobium meliloti 1021, which is able to form nitrogen-fixing nodules on its legume host plants and therefore has a very complex phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 39 publications
0
70
0
Order By: Relevance
“…The lipids were extracted according to Bligh & Dyer (1959). The chloroform phase was used for lipid analysis on TLC plates and, after one-dimensional separation (de Rudder et al, 1997), visualization of labelled compounds was obtained by autoradiography.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lipids were extracted according to Bligh & Dyer (1959). The chloroform phase was used for lipid analysis on TLC plates and, after one-dimensional separation (de Rudder et al, 1997), visualization of labelled compounds was obtained by autoradiography.…”
Section: Methodsmentioning
confidence: 99%
“…In this latter reaction, labelled methyl groups can be incorporated into phospholipids, especially into PE and to some extent into PC (de Rudder et al, 1997). However, for formation of MMPE and DMPE, methylation of the ethanolamine head group of PE is required, as this constitutes the only pathway of MMPE and DMPE formation, at least in S. meliloti (de Rudder et al, 1997). Therefore, the formation of radiolabelled MMPE and DMPE is indicative of a functional PMT pathway.…”
Section: Methylation Of Lipids In Burkholderia Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sinorhizobium meliloti, a single gene coding for Pmt activity constitutes the methylation pathway . Apart from the methylation pathway, a second bacterial pathway for PC biosynthesis exists in this organism (de Rudder et al, 1997) involving the novel enzymatic activity, phosphatidylcholine synthase (Pcs), which forms PC directly from choline and CDP-diacylglycerol (de Rudder et al, 1999;Sohlenkamp et al, 2000). We have also shown that PC is required for normal growth of S. meliloti .…”
Section: Introductionmentioning
confidence: 86%
“…The lipids were extracted according to the method of Bligh and Dyer (1959). The chloroform phase was used for lipid analysis on TLC plates and, after one-dimensional or two-dimensional separation, the individual lipids were quantified as described previously (de Rudder et al, 1997).…”
mentioning
confidence: 99%